An Analysis of Partial DNA Sequence of Meisa1 Gene on Sweet and Bitter Cassavas (Manihot esculenta Crantz.) - Dewi Indriyani Roslim; Fitriyatun Nisa; Herman Herman (Biosaintifika: Journal of Biology & Biology Education, 2016)
Sweet and bitter taste on cassava tuber is affected by starch metabolisms. Meisa1 gene is a gene in cassava (Manihot esculenta Crantz.) encoding isoamylase1 enzyme involved in starch metabolisms. This study aimed to analyze partial DNA sequences of Meisa1 gene on sweet and bitter cassavas collected by Genetics Laboratory, Department Biology, Faculty of Mathematics and Natural Sciences, Riau University, Indonesia. Methods included total DNA extraction from fresh young leaves of cassava using CTAB buffer, polymerase chain reaction (PCR), electrophoresis, and sequencing. The obtained data were analyzed using MEGA software version 5. The results showed that there were nucleotide variations in the intron region, not in the exon region. The variations were caused by the transition substitution mutation (35.39%) and transversion substitution mutation (64.61%). The genetic distance range between seven cassava genotypes was approximately 0% to 11%. Partial DNA sequence variations of Meisa1 gene located in intron region were unable to cluster seven cassava genotypes separately into two groups based on tuber taste.How to CiteRoslim, D., Nisa, F., Herman, H. (2016). An Analysis of Partial DNA Sequence of Meisa1 Gene on Sweet and Bitter Cassavas (Manihot esculenta Crantz.). Biosaintifika: Journal of Biology Biology Education, 8(1) 103-110.